Minecraft : essential handbook - Milton, Stephanie; Soares, Paul, Jr.; Maron, Jordan, 1992- (New York : Scholastic, Inc., 2014)
With tips from Minecraft experts, including developer Jeb and creator Notch himself, this is the definitive guide to surviving your first few days in Minecraft.
IG1010
Keywords: Minecraft (Game) -- Handbooks, manuals, etc; Mining engineering -- Computer games -- Handbooks, manuals, etc; Building -- Computer games -- Handbooks, manuals, etc; Computer adventure games -- Handbooks, manuals, etc; Video games -- Handbooks, manuals, etc